NATIONAL AND FOREIGN EXPERIENCE IN THE INTRODUCTION OF SPECIAL LEGAL REGIMES IN SPECIAL ECONOMIC ZONES - Abdullaeva Nodira Odilovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article is theoretical about special economic zones and economic fundamentals are described. The experience of foreign countries (People’s Republic of China, Dubai, Ireland) in the development of special economic zones was analyzed and relevant conclusions were drawn. It also draws conclusions and recommendations for further improvement of the system of organizational structures of special economic zones.